2021
DOI: 10.3390/jof7020135
|View full text |Cite
|
Sign up to set email alerts
|

Hungry for Sex: Differential Roles for Ustilago maydisb Locus Components in Haploid Cells vis à vis Nutritional Availability

Abstract: Mating-types allow single-celled eukaryotic organisms to distinguish self from non-self in preparation for sexual reproduction. The components of mating-type loci provide initial self/non-self-recognition through pheromone and receptor interactions that control early cell fusion events. However, they may also provide a second level of scrutiny that requires differences in alleles leading to production of a transcription factor required for successful downstream developmental pathways after initial cell fusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Wallen and coworkers investigated the gene–gene interaction between the b mating type genes and ump2 encoding an ammonium transporter of U. maydis . They found that bE and bW were expressed to different levels in different haploid strains starved of ammonium, and that bE and bW had different effects on the expression of genes needed for mating and pathogenicity [ 18 ]. Finally, T. Kijpornyongpan and M.C.…”
Section: Basic Biology—smut Basic Biology Understoodmentioning
confidence: 99%
“…Wallen and coworkers investigated the gene–gene interaction between the b mating type genes and ump2 encoding an ammonium transporter of U. maydis . They found that bE and bW were expressed to different levels in different haploid strains starved of ammonium, and that bE and bW had different effects on the expression of genes needed for mating and pathogenicity [ 18 ]. Finally, T. Kijpornyongpan and M.C.…”
Section: Basic Biology—smut Basic Biology Understoodmentioning
confidence: 99%
“… The role of autophagy and vacuolar proteases PrA and PrB in the pathosystem of U. maydis , M. oryzae , and A alternata. (A) In the course of an infection by U. maydis , nitrogen scarcity promotes filamentation of haploid sporidia mediated by the bE and bW genes (in an independent and nonredundant manner) and the Ump2 transporter, probably preparing the cells for mating ( Wallen et al, 2021 ). After the mating of two compatible basidiospores, Rbf1 and bE/bW induce cell cycle arrest and dikaryotic filaments extend apically over the host tissue.…”
Section: Introductionmentioning
confidence: 99%
“…For U. maydis and other fungi, carbon stress conditions existing at distinct stages of the fungal life cycle are able to cause cellular reprogramming, which can be provoked by a number of conditions. For example, the mating process involving the conjugation and fusion of two complementary sporidia of U. maydis is preferably carried out under conditions of starvation or a low nitrogen concentration ( Wallen et al., 2021 ). Apart from its participation in the fungal response to stress conditions, autophagy might play a relevant role in the uniparental inheritance of a2 mitochondria in U. maydis .…”
Section: Introductionmentioning
confidence: 99%